2019
DOI: 10.7150/ijbs.29009
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Promotes the Survival of Random-Pattern Skin Flaps by Inducing Autophagy via the AMPK-mTOR-TFEB signaling pathway

Abstract: Random-pattern skin flaps are widely used to close defects in reconstructive and plastic surgeries; however, they are vulnerable to necrosis, particularly in the distal portion of the flap. Here, we examined the effects of metformin on flap survival and the mechanisms underlying these effects. Following metformin treatment, the survival area, blood flow, and number of microvessels present in skin flaps were increased on postoperative day 7, whereas tissue edema was reduced. In addition, metformin promoted angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…By confirming that the blood vessels were amputated, separated flaps were inserted to the original position and sutured with a 7-0 nonabsorbable suture. The random skin area was equally separated into three zones from the pedicle to the distal: proximal (area I), intermediate (area II), and distal (area III) [ 3 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…By confirming that the blood vessels were amputated, separated flaps were inserted to the original position and sutured with a 7-0 nonabsorbable suture. The random skin area was equally separated into three zones from the pedicle to the distal: proximal (area I), intermediate (area II), and distal (area III) [ 3 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…On day 3, day 5, and day 7, all mice were anesthetized and placed in a warm and quiet room, and the laser Doppler instrument (Moor Instruments, Axminster, UK) was used to scan mice in each group. The infrared Doppler scanning probe scanned the area of the skin flap to record the blood flow distribution as described in the previous literature [ 3 , 9 ]. Blood flow of the skin flap was visualized with the strong signal (green, yellow, and red shown in pictures) and quantified with Moor LDI Review software (ver 6.1; Moor Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies from the same group have demonstrated that LKB1/AMPK regulates angiogenesis in response to ischemic injury in hind limbs of mice [51,52]. Many of later studies have corroborated the positive role of AMPK in angiogenesis or protective effects on endothelial cells under such circumstances as hypoxia, ischemia, stroke, and oxidative stress, and in response to cytokines and pharmacological agents such as AICAR, metformin and statins [34,43,44,45,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69].…”
Section: Positive Regulation Of Angiogenesis By Adenosine 5′-monopmentioning
confidence: 99%